Plan de negocios para la fabricación y comercialización de duvets duales elaborados con fibra de alpaca y plumón en la ciudad de Quito - Vallejo Mariño, María Belén (2019)
This project aims to analyze the feasibility, viability and profitability of the business plan for manufacturing and marketing of dual duvets in the city of Quito. A dual duvet is a type of bed cover that is characterized by generating two thermal sensations since, in its composition, it contains alpaca fiber as a filling in half of the product and featherbed in the other half. In this way, half of the duvet will generate more heat since the alpaca fiber is one of the warmest in the world, while the featherbed is a cooler material. In market research, it appears that 87.5% of couples have difficulty reaching a consensus on the amount of household items bedding used for sleeping. Women enjoy a comfortable rest when they are more sheltered while men prefer to sleep cooler. Based on the analysis of environments it is concluded that it is feasible to implement this project since the conditions of the textile industry are attractive for new ventures and the required initial investment of USD 81.009 is accessible for the project. Customer analysis shows that 73.4% of couples are willing to purchase a Dual duvet. In this way, the target market is made up of 14,005 couples, of married marital status and free union, of the socioeconomic strata A, B and C + of the city of Quito. Finally, the financial evaluation demonstrates the viability and profitability of the project. The NPV is positive with a value of USD 18.050.74, and the ROE has a rate of 8.9% from the second year, which means that investors will get from every dollar invested USD 0.089 profit.